The Legal Operation of Liens: Theory and Practice - Wiese, Mitzi (Potchefstroom Electronic Law Journal, 2021)
The legal operation of liens has been the source of academic debates for many years. Liens are traditionally classified as enrichment liens and debtor-and-creditor liens (contractual liens). In the instance of an enrichment lien the creditor (lienholder) has a contract with a non-owner and not with the owner (debtor) himself. Consequently, the creditor can vest a lien against the owner of the thing only on the grounds of unjustified enrichment. Enrichment liens are classified as real rights. In the instance of a debtor-and-creditor lien (contractual lien) the creditor (lienholder) has a contract with the owner of the thing and the contract is the basis for the liability of the owner (debtor) towards the creditor. Debtor-and-creditor liens are generally classified as personal rights. This classification causes confusion regarding the legal operation on the one hand of an enrichment lien as a real right and on the other hand of a debtor-and-creditor lien (contractual lien) as a personal right. This paper proposes that the origin of the legal claim for which the lien serves as security (unjustified enrichment or contractual) merely determines the debt (expenses) for which a lienholder can vest his lien and does not determine the classification of a lien as either a real right or a personal right. A lien can be described as a defence against the owner’s rei vindicatio and is, in principle, enforceable only against the owner of the thing (security object). A lien can, however, also be enforced against parties other than the owner, including the creditors (who, for example, want to attach the thing subject to the lien) of the owner (debtor) and other real claimants. The enforcement of a lien against these parties is referred to as the real operation (third-party action) of a lien. This paper analyses the legal operation of a lien with specific reference to the debt (expenses incurred) secured by the lien, the vesting (existence) of a lien, the real operation (third-party action) of a lien and the preferential position of a lienholder in the case of the debtor’ insolvency.